Comparative Phytochemical Screening and Pharmacognostic Study on Stem Bark and Root bark of Endangered Medicinal Plant Oroxylum indicum (L.) Vent - Rajak, Virendra; Pathak, Vandana; Tripathi, Manoj (International Journal of Scientific Research in Biological Sciences, 2018)
Medicinal plants are an important component of natural resources and they are used as a source of food, medicine, fibres, tannin, gum and allied uses. Oroxylum indicum (L.) Vent. (Bignoniaceae) also known as ‘Sonapatha’ is an important endangered medicinal plants of indigenous medical system for over hundreds of years. It has been used as a single drug and as a component for preparation of ayurvedic compound preparations viz. Dashmularistha and Chyavanprash etc. Plants are used in treating in various human ailments like jaundice, dysentery, asthma, allergic disease, urticaria, sore throat, measles, laryngitis, hoarseness and diarrhea. The present paper provides a detailed account of the phytochemical evaluation and pharmacognostic studies of Sonapatha stem bark and rroot bark. The study includes macroscopy, microscopy, and powder microscopy studies, fluorescence study, physicochemical parameters, preliminary phytochemical screening High Performance Thin Layer Chromatography fingerprint profile. Established parameters can be used as standards for identification and quality control of the plants in compound formulations and also preparation of a monograph of the plant.